2009
DOI: 10.1007/s00244-009-9401-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Deltamethrin on Antioxidant Defense Mechanisms and Lipid Peroxidation in Carassius auratus gibelio Liver and Intestine

Abstract: Pyrethroids, such as deltamethrin, are toxic substances that lead to generation of reactive oxygen species, which harm living organisms. We assessed the level and patterns of imbalance evolved by a single dose of 2 microg/L deltamethrin on the lipid peroxidation (LPO) and the antioxidant defense system of Carassius auratus gibelio liver and intestine, and monitored the recovery dynamics of these parameters during a 14-day post-exposure period. LPO and antioxidative defense mechanisms displayed different respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 44 publications
5
16
0
Order By: Relevance
“…Similar results were also observed in the livers of Carassius auratus injected intraperitoneally with 17 different phthalates at a concentration of 10 mg/kg for 10 days [25]. Many previous studies have shown that oxidative stress status is interrelated with pollutant exposure, which is a possible regulation of the toxicity of these chemicals [52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were also observed in the livers of Carassius auratus injected intraperitoneally with 17 different phthalates at a concentration of 10 mg/kg for 10 days [25]. Many previous studies have shown that oxidative stress status is interrelated with pollutant exposure, which is a possible regulation of the toxicity of these chemicals [52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 79%
“…In another study, deltamethrin was observed to be significantly inhibiting rainbow trout carbonic anhydrase enzymes invitro and invivo (Ekinci and Beydemir 2010). It was reported that deltamethrin caused gradual decrease on activities of different antioxidant enzymes in the first 3 days (Dinu et al 2010). Similar inhibition in metabolic enzyme activities in C. catla fingerlings were reported (Vani et al 2011).…”
Section: Biochemical and Hematological Alterationsmentioning
confidence: 71%
“…Recent studies indicate that pesticide intoxication produce oxidative stress by the generation of free radicals and induce tissue lipid peroxidation in mammals and other organisms [27][28][29]. In addition, free radicals have been shown to be key mediators of myocardial reperfusion injury and lipid peroxidation [30].…”
Section: Discussionmentioning
confidence: 99%